Creating Women Characters in Horror Films using AI: Avoiding Male Gaze Characters Template - Sofiyanti, Devina; Irwanto, Irwanto (ULTIMART Jurnal Komunikasi Visual, 2024)
In screenwriting, one of the most essential elements is character. Characters are usually shaped by three critical factors: physical appearance, psychology, and sociology. In horror films, female characters are often used as protagonists, but in the history of horror films, female characters are trapped by the male gaze. The male gaze functions as a mechanism to dehumanize and commodify women, viewing them solely through the lens of heterosexual male desire. Laura Mulvey, in her seminal 1975 essay "Visual Pleasure and Narrative Cinema," posits that films serve to strengthen patriarchal structures by portraying women as mere objects for both the male protagonist inside the film and the audience consuming the film. The use of AI in screenwriting continues to grow, although it is still a matter of debate. As we know, AI works by gathering and generalizing information from pre-existing data. This becomes a problem when we want to create female characters that are not considered male-gaze. Of course, not all horror films that have been made use the male gaze, but we must understand how horror films develop occasionally. This paper examines the relationship between artificial intelligence and creating female characters in scriptwriting, especially horror films. A conceptual paper is a paper without data, as it is focused on “integration and proposing new relationships among constructs”.This paper also aims to find the next step for us to create women characters with AI. Keywords: AI; scriptwriting; character; male gaze; horror